Family Size And Health Insurance Premium Payment Compliance: A Study Of Non-Wage Workers In Samarinda City - Fadlillah, Muhammad Ridho; Adrianto , Ratno; Wisnuwardani, Ratih Wirapuspita (Jurnal Riset Kesehatan Nasional, 2025)
The irregular income patterns and financial vulnerabilities of non-wage worker (PBPU) participants in Indonesia's National Health Insurance (JKN) program pose challenges to premium payment compliance. As of September 2023, only 40.3% of Samarinda City's 348,434 PBPU participants actively paid premiums, highlighting the issue. This study analyzed the association between family size and premium payment compliance among 76,773 PBPU families in Samarinda using a retrospective cross-sectional design and chi-square tests. Results revealed a significant relationship between larger families and arrears (p-value = 0.000). The findings emphasize the need for targeted interventions, such as tiered payment schemes for larger families, flexible payment options, and financial support mechanisms to enhance compliance. Future research should explore additional socioeconomic factors across regions to develop more comprehensive solutions for sustaining the JKN program. Keywords: National Health Insurance, Non-Wage Workers, Registered Family, Premium Payment